Analyses of gene expression profiles in the rat dorsal horn of the spinal cord using RNA sequencing in chronic constriction injury rats - Hui Du; Juan Shi; Ming Wang; Shuhong An; Xingjing Guo; Zhaojin Wang (Journal of Neuroinflammation, 2018)
Abstract Background Neuropathic pain is caused by damage to the nervous system, resulting in aberrant pain, which is associated with gene expression changes in the sensory pathway. However, the molecular mechanisms are not fully understood. Methods Wistar rats were employed for the establishment of the chronic constriction injury (CCI) models. Using the Illumina HiSeq 4000 platform, we examined differentially expressed genes (DEGs) in the rat dorsal horn by RNA sequencing (RNA-seq) between CCI and control groups. Then, enrichment analyses were performed for these DEGs using Gene Ontology (GO) function, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway, Hierarchical Cluster, and protein-protein interaction (PPI) network. Results A total of 63 DEGs were found significantly changed with 56 upregulated (e.g., Cxcl13, C1qc, Fcgr3a) and 7 downregulated (e.g., Dusp1) at 14 days after CCI. Quantitative reverse-transcribed PCR (qRT-PCR) verified changes in 13 randomly selected DEGs. GO and KEGG biological pathway analyses showed that the upregulated DEGs were mostly enriched in immune response-related biological processes, as well as 14 immune- and inflammation-related pathways. The downregulated DEGs were enriched in inactivation of mitogen-activated protein kinase (MAPK) activity. PPI network analysis showed that Cd68, C1qc, C1qa, Laptm5, and Fcgr3a were crucial nodes with high connectivity degrees. Most of these genes which have previously been linked to immune and inflammation-related pathways have not been reported in neuropathic pain (e.g., Laptm5, Fcgr3a). Conclusions Our results revealed that immune and defense pathways may contribute to the generation of neuropathic pain after CCI. These mRNAs may represent new therapeutic targets for the treatment of neuropathic pain.